Hubungan Tingkat Pengetahuan Dengan Gejala Keracunan Pestisida pada Petani Penyemprot Pestisida Tanaman Holtikultura di Kecamatan Lembah Gumanti Kabupaten Solok Tahun 2019 - Fadillah Ulva; Nurul Prihastita Rizyana; Afzahul Rahmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The World Health Organization (WHO) and The United Nations Environment Program (UNEP) predict there are 1.5 million cases of pesticide poisoning that occur in the agricultural sector, most of which occur in developing countries. Pesticides are hazardous and toxic materials (B3) that must be managed properly. Farmers get many benefits from using pesticides. Pesticides are used by farmers to control pest attacks. Improper using of pesticides can endanger farmers. Horticulture plants need pesticides to control pest attacks. There are various factors that can affect the level of pesticide poisoning in farmers, one of them is the level of knowledge. Lack of knowledge about pesticides will increase the risk of pesticide poisoning. The purpose of this study was to determine the relationship between the level of knowledge with symptoms of pesticide poisoning in horticultural farmers in Lembah Gumanti, Solok Regency in 2019. The type of this research was observational analytic research with cross sectional design. The population in this study were all horticultural farmers in the Gumanti Lembah Subdistrict of Solok Regency in 2018 totaling 128 people with a sample of 56 people. The sample is done by proportional random sampling technique. Data analysis was carried out by univariate and bivariate. The results showed that 41.1% of respondents had symptoms of risky poisoning, 46.4% of respondents knowledge was still low. Based on statistical tests it is known that there is a significant relationship between the level of knowledge with symptoms of pesticide poisoning. It can be concluded that the level of knowledge will affect the incidence of pesticide poisoning in horticultural farmers. It can be suggested to farmers to increase knowledge regularly.